Pengembangan Modul Fisika dengan Pendekatan Sains Teknologi Masyarakat Materi Kalor untuk Siswa Kelas XI SMA/MA - Annisa Nurrul Hamsah; Sarwanto Sarwanto; Cari Cari (Universitas Sebelas Maret, 2019)
The research goals were: (1) to know the characteristics of physics module using science, technology, and society approach on lesson material about heat for eleventh grade students; (2) to know the feasibility of the physics module using science, technology and society approach on lesson material about heat; (3) to know the effectiveness of physics module using science, technology and society approach on lesson material about heat on the learning outcome at Takeran Islamic High School. This study was the research and development (R&D) which refers to Thiagarajan’s model. This research was conducted from January 2017 to May 2017. Media’s feasibility was validated by the experts and teachers’ validation. The field trial subjects in this research were 38 students from grade IX of Takeran Islamic High School in the academic year 2016/2017. 15 students were the limited trial subjects and 23 students were user trial subjects. The module was examined to the physics teachers at the school. The research data were the score of module validation from experts, teachers, students’mates, students’ readability, students’ scores, and the students’ responses. Based on the data analyzing, it was concluded that: (1) the physics module using science, technology, and society approach is a systematic learning media consisting of learning instruction, daily phenomenon, concept formation through practicum, application of concepts in technology used by society, material descriptions, and multiple choice formative tests. The module was arranged into the communicative sentences to give a good understanding to the students about the role of heat in daily life, (2) physics module using science, technology and society approach on heat material for eleventh grade students at high school which developed was stated as feasible with excellent predicate and gained scores from experts validation 279, teachers validation 307, and mates validation 324. Students’ response gained 85% on limitation trial and 90 % on field trial with excellent predicates, (3) the physics’ module of the developing product was effective to improve the learning outcomes viewed from the average of pretest score 34 and posttest score 64 with gain score 29 and normalized gain 0.29 showed that students had improved on medium predicate. It can be concluded that learning using module through science, technology and society approach obtained positive response and motivated the students. It was measured from the students who felt happy and enjoyed used the product.